Bone Components Downregulate Expression of Toll-Like Receptor 4 on the Surface of Human Monocytic U937 Cells: A Cell Model for Postfracture Immune Dysfunction - Jui-An Lin; Feng-Yen Lin; Ta-Liang Chen (Mediators of Inflammation)
To mimic the immune status of monocyte in the localized fracture region, toll-like receptor 4 (TLR4) surface expression in human monocytic U937 cells was used as the main target to assess immune dysfunction following bone component exposure. We first identified the effects of bone components (including the marrow content) on TLR4 surface expression and then examined the mechanisms underlying the changes. The level of microRNA-146a expression, an indicator of endotoxin tolerance, was also assayed. Bone component exposure downregulated TLR4 surface expression at 24 h by flow cytometry analysis, compatible with the result obtained from the membranous portion of TLR4 by western blot analysis. The cytoplasmic portion of TLR4 paradoxically increased after bone component exposure. Impaired TLR4 trafficking from the cytoplasm to the membrane was related to gp96 downregulation, as observed by western blot analysis, and this was further evidenced by gp96-TLR4 colocalization under confocal microscopy. TaqMan analysis revealed that the expression of microRNA-146a was also upregulated. This cell model demonstrated that bone component exposure downregulated TLR4 surface expression in a gp96-related manner in human monocytic U937 cells, an indicator of immunosuppression at 24 h. Immune dysfunction was further evidenced by upregulation of microRNA-146a expression at the same time point.